Introduction to the Basic Concept of Simple Financial Recording in MSMEs - Syahrizal, Muhammad; Nugroho, Very Sapto; Mardin, Mardin; Antonius, Antonius; Jaya, Andi Eka Putra; Rakhmaji, Iqbal; Sari, Maya; Masriani, Masriani; Nurlinda, Andika; Asma, Asma; Hanif, Faizira Nur (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Early financial literacy is an essential foundation for developing financial awareness and skills. This program was implemented through the Community Service Program (KKN) in Petiku Village in October 2024. The program aimed to introduce basic financial concepts to micro-entrepreneurs and improve the owners' competency in financial management. The research methods used were interviews, direct observation, and field training to identify problems and provide easy-to-implement financial record-keeping solutions. The results showed that implementing simple financial records, such as cash flow statements, profit and loss statements, and balance sheets, manually can help MSMEs better monitor their finances, make more informed business decisions, and improve operational efficiency. This study concluded that good and regular financial records are crucial for the sustainability and development of MSMEs.